Friday

October 24, 2014

October 24, 2014

Posted by **Lindsay** on Sunday, December 1, 2013 at 8:07pm.

- Math -
**Damon**, Sunday, December 1, 2013 at 8:15pm(x+h)^2-x^2 = x^2 + 2 x h + h^2 - x^2

or in other words 2 x h + h^2

or h (2 x + h)

divide that by h

2x+h

limit as h ---> 0 is

2 x

so

f(x) = 2 x as h--->0

4 = 2 x

x = 2

**Answer this Question**

**Related Questions**

calc - need to find: lim as x -> 0 of 4(e^2x - 1) / (e^x -1) Try splitting ...

Calculus - Find the following limits algebraically or explain why they don’t ...

math - i need some serious help with limits in pre-calc. here are a few ...

Math(calculus) - Evaluat d 4lowing1.lim x/|x| x-->0 2.lim x->1 sqrt(x^2+2...

Calc. Limits - Are these correct? lim x->0 (x)/(sqrt(x^2+4) - 2) I get 4/0...

calc - Are these correct? lim x->0 (x)/(sqrt(x^2+4) - 2) I get 4/0= +/- ...

Calc Please Help - Are these correct? lim x->0 (x)/(sqrt(x^2+4) - 2) I get 4/...

Calculus - Find the limit. lim 5-x/(x^2-25) x-->5 Here is the work I have so ...

CALCULUS - Evaluate each of the following. (a) lim x->0(e^x)-1-x/ x^2 (b) lim...

Probability - Let Sn be the number of successes in n independent Bernoulli ...